Neutralization of the intervocalic rhotic contrast in Northern Belizean Spanish - Balam, Osmer (Borealis – An International Journal of Hispanic Linguistics, 2013)
While it has been contended that the tap/trill intervocalic contrast has been lost in many Spanish varieties, maintenance of the normative intervocalic tap/trill contrast has been attested via segmental duration rather than the number of lingual contacts. The present paper investigates the neutralization of the intervocalic rhotic contrast in emerging, bi-dialectal speakers of Northern Belizean Spanish, an understudied variety of contact Spanish with innovative patterns of rhotic distribution. Acoustic analysis of data from 10 adolescent speakers from Orange Walk, Belize showed that in the elicited, oral production data, speakers were able to more consistently maintain their native Spanish variety's intervocalic tap/retroflex approximant phonemic contrast. However, in an effort to phonetically switch to a more standard variety of Spanish in the read-aloud task, speakers' overgeneralization of the tap led to neutralization of the tap/trill contrast and partial loss of their native Spanish variety's intervocalic phonemic contrast.